Modeling and Analysis of Perishable Inventory System with Retrial demands in Supply Chain (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In this article, we consider a continuous review perishable inventory system with poisson demands. The maximum storage capacity at lower echelon (retailer) is S and the upper Echelon (Distribution Center) is M (= nQ). The life time of each item is assumed to be exponential. The operating policy is (s, S) policy, that is, whenever the inventory level drops to s, an order for Q = (S - s > s) item is placed. The ordered items are received after a random time which is distributed as exponential. We assume that demands occurring during the stock-out period enter into the orbit. These orbiting demands send out signal to complete for their demand which is distributed as exponential. The joint probability distribution of the inventory level at retailer, inventory level at DC and the number of demands in the orbit are obtained in the steady state case. Various system performance measures are derived and the results are illustrated numerically.